Retroperitoneal Endometriotic Cyst Infiltrated in the Iliopsoas Incidentally Found in a Patient with Acute Back Pain - Nanami Tsukasaki; Takuro Yamamoto; Akihisa Katayama; Nozomi Ogiso; Tomoharu Okubo (Case Reports in Obstetrics and Gynecology)
We describe a rare case of retroperitoneal endometriotic cyst infiltrated in the iliopsoas incidentally found in a patient with acute back pain. Endometriosis at the pelvic peritoneum, including the Douglas pouch, has been reported often; there are few reports of cystic endometriosis in the retroperitoneal cavity. Today there are various theories regarding how endometriosis occurs. By pathological findings and lesion sites of the present case, we concluded that the endometrial tissues in the menstrual blood might metastasize lymphatically and implant and form the retroperitoneal cyst.